Characteristics of Latino MSM who have Sex in Public Settings - Reisen, Carol A (2011)
Many men who have sex with men (MSM) have sexual encounters in public places, and some data suggest that this behavior is more common among Latino than non-Hispanic white MSM in the U.S. In a sample of 482 Latino MSM born in Brazil, Colombia, and the Dominican Republic, and living in the New York City metropolitan area, we examined how demographic and psychosocial characteristics are related to having sex in public venues. Logistic regression was performed with the dichotomous outcome of sex in a public place in the previous six months. Demographic variables included education, HIV-positive serostatus, unknown HIV serostatus, and having immigrated to the U.S. within the previous five years; psychosocial variables included self-efficacy for safer sex, depression, and gay community involvement. Results indicated that those individuals with unknown serostatus were more likely than those with HIV-negative serostatus to have had sex in a public setting, as were men with lower self-efficacy for safer sex. These findings suggest that the partner pool in public sex venues may pose substantial risk, and therefore they underscore the importance of low risk sexual practices and condom use in such settings. Contrary to expectations, higher education was related to sex in public settings, but neither depression nor recent immigration was. Greater involvement in the gay community was also associated with having sex in public places, which may reflect the larger social function served by gay venues such as bathhouses and bars.